ELLA DURRAN'S SELF-FORMATION IN JULIA WHELAN'S MY OXFORD YEAR - Rafi Husain; Adelie Grace Marianne litaay (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This article analyzes the self-formation of Ella Durran in Julia Whelan's My Oxford Year (2018) through Anthony Giddens' Reflexive Project of the Self. Using Giddens' framework from Modernity and Self-Identity (2020), the study examines how Ella constructs, disrupts, and revises her self-narrative through romantic experience. The study addresses three research questions: (1) How does romantic love initiate Ella Durran's self-formation? (2) How does suffering through love deepen Ella's personal growth? (3) How does love's loss complete Ella's transformation into a fully formed self? Giddens argues that in late modernity the self is not a fixed entity but an ongoing reflexive project, sustained through a continuously revised biographical narrative. The qualitative close reading and thematic coding of the primary text reveal that Ella's trajectory follows three interlocking phases of self-formation. In the first phase, her encounter with Jamie Davenport functions as a fateful moment that disrupts her defended, future-oriented identity. In the second phase, loving Jamie through his terminal illness generates existential confrontation with risk and mortality, producing the forms of self-knowledge that Giddens identifies as products of genuine reflexivity. In the third phase, her confrontation with the certainty of loss and her active decision to stay in Oxford constitute the reconstruction of a new self-narrative grounded in lived experience rather than inherited planning. The findings demonstrate that My Oxford Year enacts Giddens' reflexive model with formal coherence.